Cell-free supernatant of probiotic bacteria exerted antibiofilm and antibacterial activities against Pseudomonas aeruginosa: A novel biotic therapy - Drumond, Mariana Martins; Tapia-Costa, Ana Paula; Neumann, Elisabeth; Nunes, Álvaro Cantini; Barbosa, Jorge Wanderson; Kassuha, Diego E.; Mancha-Agresti, Pamela (Frontiers in Pharmacology, 2023)
Aim: This study aims to verify the antibacterial and antibiofilm action of cell-free spent medium (CFSM) from four lactic acid bacteria with potential probiotic characteristics (Lactiplantibacillus plantarum, Lactobacillus acidophilus, Lactobacillus johnsonii, and Lactobacillus delbrueckii) against two Pseudomonas aeruginosa strains. Main methods: The minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) of the CFSM, antibacterial activity by analysing the formation of inhibition zones, and inhibition of planktonic cultures were determined. Whether an increase in the concentration of CFSM influenced the growth of pathogenic strains and the anti-adhesive activity of the CFSM in biofilm formation (crystal violet and MTT assays) were determined, which were all corroborated by using scanning electron microscopy. Key findings: The relationship between the MIC and MBC values showed a bactericidal or bacteriostatic effect for all the cell-free spent media (CFSMs) tested for P. aeruginosa 9027™ and 27853™ strains. The CFSM supplemental doses of 18 or 22%, 20 or 22%, 46 or 48%, and 50 or 54% of L. acidophilus, L. delbrueckii, L. plantarum, and L. johnsonii, respectively, could completely inhibit the growth of both pathogen strains. The antibiofilm activity of the CFSM in three biofilm conditions (pre-coated, co-incubated, and preformed) demonstrated values ranging between 40% and 80% for biofilm inhibition, and similar results were observed for cell viability. Significance: This work provides strong evidence that the postbiotic derived from different Lactobacilli could be practical as an adjuvant therapy for reducing the use of antibiotics, being a good candidate to overcome the growing challenge of hospital infections due to this pathogen.